(untitled) - Skrypuch, Marsha Forchuk (Ontario, Canada, 1999)
The Hunger is a beautifully written account of one young woman's journey to find out about her heritage while she struggles with the very real issues of anorexia. It appeals to all generations and helps to guide the reader from present-day realities to the realities of history.
Keywords: Armenian massacres, 1915-1923; Juvenile fiction